Experimental study on potential use of photochromic thin film as energy harvester - Wahid, Zaharah; Za'bah, Nor Farahidah; Ahmad, Kartini; Yasin, Nabila Huda (AENSI, 2015)
This paper presents the application of design of experiments (DOE) in the characterization of the photochromic thin film after irradiation to UV light and designing of a circuit as a potential energy harvester. The results from this study suggest that exposure time at high level and interaction between exposure time and thickness of thin film have the largest influence on the mean voltage, while the thickness of thin film by itself does not affect the mean voltage. This study has provided a comprehensive knowledge and enhanced understanding for choosing the appropriate factors and levels in characterization of a photochromic film as a potential energy harvester.